Differences in Short QT Syndrome Subtypes: A Systematic Literature Review and Pooled Analysis - Raschwitz, Laura S.; El-Battrawy, Ibrahim; Schlentrich, Kim; Besler, Johanna; Veith, Michael; Roterberg, Gretje; Liebe, Volker; Schimpf, Rainer; Lang, Siegfried; Wolpert, Christian; Zhou, Xiaobo; Akin, Ibrahim; et al. (Frontiers in Genetics, 2020)
Abstract Background Short QT syndrome (SQTS) is a rare syndrome and affects different types of genes. However, data on differences of clinical profile and outcome of different SQTS types are sparse. Methods We conducted a pooled analysis of 110 SQTS patients. Patients have been diagnosed between 2000 and 2017 at our institution (n=12) and revealed using a literature review (n=98). 29 studies were identified by analysing systematic data bases (PubMed, Web of Science, Cochrane Libary, Cinahl). Results 67 patients with genotype positive SQTS origin and 43 patients with genotype negative origin were found. A significant difference is documented between the sex with a higher predominance of male in genotype negative SQTS patients and predominance of females in genotype positive SQTS patients (male 52% versus 84%, p=0.0016; female 45% versus 14%; p=0.0016). No relevant difference of their median age (genotype positive 27±19 versus genotype negative 29±15; p=0.486) was found. Asymptomatic patients and patients reporting symptoms such as syncope, sudden cardiac death, atrial flutter and ventricular fibrillation documented in both groups were similar except atrial fibrillation (genotype positive 19% versus genotype negative 0%; p=0.0055). The QTc interval was not significantly different in both groups (genotype positive 315±32 versus genotype negative 320±19; p=0.302). The treatments (medical treatment and ICD implantation) in both groups were comparable. Electrophysiology studies were not significantly higher documented in patients with genotype positive and negative origin (24 % versus 9%; p=0.0754). Events at follow up such as VT, VF, and SCD were higher presented in patient with genotype positive (13% versus 9%) but not significantly (p= 0.2554). 54% of genotype positive SQTS patients showed SQTS 1 followed by STQS 2 (21%) and SQTS 3 (10%). Conclusions The long-term risk of a malignant arrhythmic event is not higher in patients with genotype positive. However, patients with genotype positive present themselves more often with AF with a female predominance. Also, other events at follow up such as syncope, atrial flutter and palpitation were not significantly higher (9% versus 0%; p=0.0796).